Genome-wide identification of microRNAs and their targets in wild type and phyB mutant provides a key link between microRNAs and the phyB-mediated light signaling pathway in rice - Sun, Wei; Xu, Xiao Hui; Wu, Xiu; Wang, Yong; Lu, Xingbo; Sun, Hongwei; Xie, Xianzhi (Frontiers in Plant Science, 2015)
Phytochrome B (phyB), a member of the phytochrome family in rice, plays important roles in regulating a range of developmental processes and stress responses. However, little information about the mechanisms involved in the phyB-mediated light signaling pathway has been reported in rice. MicroRNAs (miRNAs) also perform important roles in plant development and stress responses. Thus, it is intriguing to explore the role of miRNAs in the phyB-mediated light signaling pathway in rice. In this study, comparative high-throughput sequencing and degradome analysis were used to identify candidate miRNAs and their targets that participate in the phyB-mediated light signaling pathway. A total of 720 known miRNAs, 704 novel miRNAs and 1,957 target genes were identified from the fourth leaves of wild-type (WT) and phyB mutant rice at the five-leaf stage. Among them, 135 miRNAs showed differential expression, suggesting that the expression of these miRNAs is directly or indirectly under the control of phyB. In addition, 32 out of the 135 differentially expressed miRNAs were found to slice 70 genes in the rice genome. Analysis of these target genes showed that members of various transcription factor families constituted the largest proportion, indicating miRNAs are probably involved in the phyB-mediated light signaling pathway mainly by regulating the expression of transcription factors. Our results provide new clues for functional characterization of miRNAs in the phyB-mediated light signaling pathway, which should be helpful in comprehensively uncovering the molecular mechanisms of phytochrome-mediated photomorphogenesis and stress responses in plants.